Improving The Methodological Training Of Future Teachers Based On Interdisciplinary Integration - Barno Abdullaeva, Nazokatkhon Yusupova (International Journal of Advanced Science and Technology, 2020)
The article discusses the main aspects of preparing students of pedagogical universities for interdisciplinary training of future primary school students. The effectiveness of the implementation of integrative learning in preparing a future teacher for future professional activity in learning will be higher if at its stages contextual and personal-activity approaches based on the task approach are implemented. The content of the educational process aimed to include problem-diagnostic task material affecting aspects of pedagogical activity, regarding which there are no final solutions, as a result of which the educational process is presented as a consistent development of creative experience and an independent position of a future teacher. Mastering the experience of creating a pedagogical situation is ensured in experimental work by reproducing a practice-oriented technology in the educational process, implementing individual routes for mastering pedagogical generalized skills on the basis of various forms of integration of disciplines of general professional and subject cycles of training programs.